2013
DOI: 10.1080/07481187.2013.780113
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Vulnerability to Suicide in the Developmental History of Young Men: A Psychological Autopsy Study

Abstract: This study explores the developmental history of ten young men who completed suicide in the transition to adulthood. The young men, aged 18-30, had no previous history of suicide attempts or treatment in mental health. In-depth interviews with four to eight informants for each suicide were analyzed using Interpretative Phenomenological Analysis. Three developmental issues from early age onwards emerged: (a) unsuccessful in becoming independent; (b) weakened competence to deal with shame; and (c) trapped in ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 20 publications
3
20
0
4
Order By: Relevance
“…The most frequently used strategy to identify eligible participants was through suicide registries and death records (n = 4, 33%)[3134]. Samples were from prison inmate populations (n = 4, 33%), psychiatric wards (n = 2, 17%), self-selection from the wider population (n = 2, 17%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently used strategy to identify eligible participants was through suicide registries and death records (n = 4, 33%)[3134]. Samples were from prison inmate populations (n = 4, 33%), psychiatric wards (n = 2, 17%), self-selection from the wider population (n = 2, 17%).…”
Section: Resultsmentioning
confidence: 99%
“…Anger [34,42], direct statements of suicidal intent [33,44], and paucity of problem solutions [33,42] were common signs associated with male deaths by suicide (see Table 2). Rasmussen et al [33] also found that in the days prior to death by suicide, many informants reported that conversations with the deceased were marked by an absence of negative mood, or the emergence of a more positive mood state, in addition to agitation, the perception of death as a problem solution, desperation and reaching out for support in desperation.…”
Section: Resultsmentioning
confidence: 99%
“…Istedenfor å senke prestasjonskravene i slike situasjoner ble de overmannet av sterke følelser, spesielt skam og sinne, som de verken var i stand til å regulere eller håndtere. Den tidligere strategien som innebar kompensasjon ved stadig å øke prestasjonene, fungerte ikke lenger, og selvmordet ble veien ut av en tilstand av uutholdelig psykisk smerte (12).…”
Section: Som Man Spør Får Man Svar?unclassified
“…Én uheldig konsekvens er at det kan bre seg en oppfatning om at så lenge det ikke er tegn til psykisk sykdom, er det ingen fare på ferde (14). Som det går frem av Rasmussen og kollegers studie (12), kan dette bli skjebnesvangert.…”
Section: Er Det Så Farlig Da?unclassified
“…Å forhindre selvmord og selvmordsforsøk er krevende, men ikke umulig. Forebyggende innsats rettet mot utsatte grupper er vesentlig, men siden selvmord ikke bare forekommer hos personer med typiske risikofaktorer, må forebyggende innsats favne videre (Rasmussen et al, 2013). En befolkning med et våkent blikk for mulig selvmordsatferd vil kunne vaere med på å redde liv.…”
unclassified